The Effect of Shopee Flash Sale Program on Financial Management - Putri, Kessa Mindabila; Aswat, Ibnu; Astarani, Juanda (Jurnal Ilmiah Manajemen Kesatuan, 2024)
The use of e-commerce has become a rampant phenomenon among college students, with rapid growth in recent years. One e-commerce that is widely used by students is Shopee. Shopee flash sales have become a popular marketing strategy on e-commerce platforms, with the aim of increasing sales and attracting consumer interest. This research aims to analyze the influence of the Shopee Flashsale phenomenon on students' financial spending patterns in online shopping and the Flashsale factors that influence consumer behavior on the Shopee platform. The research method used was an online survey and observation of flash sale activities at Shopee involving a sample of students at the economics and business faculty. The analysis results show that flash sales on Shopee have a significant impact on increasing student financial expenditure. Factors such as discount twin date promos, and free shipping vouchers. Additionally, there are certain patterns in consumer behavior during flash sales, including an increase in the number of visits to the platform, an increase in impulse purchases, and an increase in social interaction through in-app communication features. The convenience of online shopping, competitive prices, wide product variations, and attractive promotions collectively influence students' decisions in making online purchases. Additionally, aspects such as trust in e-commerce platforms, product quality, and user experience also play an important role in shaping college students' online shopping preferences.